2022
DOI: 10.1002/alz.069052
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance and robustness of blood‐based biomarkers for early detection of amyloid pathology associated with Alzheimer’s disease

Abstract: BackgroundAccurate and robust blood‐based biomarkers (BBBMs) of Alzheimer’s disease (AD) are required for identification of symptomatic patients with low likelihood of amyloid pathology before confirmatory diagnostic evaluation. Further evidence on the clinical performance and robustness of BBBMs is required to identify patients for clinical trials and in routine clinical practice. We evaluated the clinical performance and robustness of amyloid‐β 1–42 (Aβ42), amyloid‐β 1–40 (Aβ40), apolipoprotein E4 (ApoE4), p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The Elecsys Amyloid Plasma Panel is based on a retrospective study that assessed a panel of Elecsys prototype immunoassays for clinical performance and robustness in three cohorts. It was found that the p‐tau181 and apolipoprotein E4 composite plasma biomarker score was the best‐performing combination in terms of meeting the clinical performance and robustness requirements to rule out symptomatic individuals with a low likelihood of Aβ pathology 51 …”
Section: Potential Clinical Value Of Plasma Biomarker Testing In the ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The Elecsys Amyloid Plasma Panel is based on a retrospective study that assessed a panel of Elecsys prototype immunoassays for clinical performance and robustness in three cohorts. It was found that the p‐tau181 and apolipoprotein E4 composite plasma biomarker score was the best‐performing combination in terms of meeting the clinical performance and robustness requirements to rule out symptomatic individuals with a low likelihood of Aβ pathology 51 …”
Section: Potential Clinical Value Of Plasma Biomarker Testing In the ...mentioning
confidence: 99%
“…50 High robustness indicates that diagnostic performance is unaffected by small differences in test conditions such as pre-analytical sample handling techniques, analytical variability, lab-to-lab, batch-to-batch, and operator differences, all of which are unavoidable in practice. 51 Clinical validation assesses whether the test serves its purpose in the intended use population, that is, whether the test is able to reliably diagnose people with the condition and, in doing so, inform clinical decision making. In real-world terms, a widely validated test with high robustness means that patients are less likely to be misclassified and, hence, are more likely to receive the correct support and treatment.…”
Section: Defining Ivds Ldts and Ruosmentioning
confidence: 99%
See 1 more Smart Citation